Short-Term Employment Persistence for Welfare Recipients: The "Effects" of Wages, Industry, Occupation and Firm - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1997)
Using data from 13 years (1983-95) of the March Current Population Survey, this study examines how the types of jobs held by welfare mothers during the preceding year affects their employment and earnings at the time of the March interview. The estimates suggest that the Using data from 13 years (1983-95) of the March Current Population Survey, this study examines how the types of jobs held by welfare mothers during the preceding year affects their employment and earnings at the time of the March interview. The estimates suggest that the wages of last year's job affect current employment and earnings, but the effects of wages are more modest than might be expected. The industry and occupation of last year's job make a great deal of difference, with industry being more important than occupation. The industries with the most positive effects on current employment are hospitals and educational services; jobs held last year in the temporary help industry are negatively correlated with current employment. The size of the firm employing a welfare recipient last year has no effect on March's employment or earnings. These results suggest that welfare-to-work programs should consider efforts to target higher-wage jobs or jobs in industries such as hospitals or educational services. wages of last year's job affect current employment and earnings, but the effects of wages are more modest than might be expected. The industry and occupation of last year's job make a great deal of difference, with industry being more important than occupation. The industries with the most positive effects on current employment are hospitals and educational services; jobs held last year in the temporary help industry are negatively correlated with current employment. The size of the firm employing a welfare recipient last year has no effect on March's employment or earnings. These results suggest that welfare-to-work programs should consider efforts to target higher-wage jobs or jobs in industries such as hospitals or educational services.
Keywords: J0; J4; 330; welfare; welfare-to-work; wages; Bartik